Carbon nanotube-based heterostructures for high-performance photodetectors: Recent progress and future prospects. Issue 12 (15th August 2020) - Liu, Ping; Yang, Shi-E.; Chen, Yongsheng; Ma, Yanxia; Liu, Sheng; Fang, Xiangqian; Fan, Fuling; Han, Jianxun
Abstract: Unique optical, electrical and chemical properties make carbon nanotubes (CNTs) an excellent candidate for potential applications in the next-generation optoelectronics. Especially, the optoelectronic properties of CNTs can be enhanced dramatically by constructing heterostructures with other materials, in which the charge separation efficiency is enhanced and the recombination probability of excitons is suppressed significantly. Therefore, the CNT-based heterostructures have been widely used as active materials in high-performance photoelectronic devices. Herein, the recent progress of the CNT-based heterostructure photodetectors is reviewed. Firstly, the working mechanisms and typical figures-of-merits are introduced. Secondly, different type CNT-based heterostructures and related photodetectors are highlighted, such as van der Waals heterostructures, all-carbon heterostructures, and bulk heterostructures. Finally, we give the current challenges and future prospects for the development of this emerging field.